Lesson Study and School as a Learning Community to Support Sustainable Development Goals (SDGs): Definition, Literature Review, and Bibliometric Mapping - Jiraporn Chano; Bovornpot Choompunuch; Chi Cheng Wu (ASEAN Journal of Educational Research and Technology, 2027)
This study reviews the development of research on lesson study and school as a learning community and positions bibliometric mapping as supporting evidence for understanding research trends. The review focuses on lesson study, school as a learning community, learning design, authentic learning, reflection, and embodied learning as interconnected concepts for improving teaching quality and collaborative professional learning. A literature review supported by bibliometric analysis was conducted using documents retrieved from Google Scholar through Publish or Perish and visualized using VOSviewer. Research in this field connects teacher collaboration, reflective practice, curriculum design, professional development, and student-centered learning. Bibliometric results show publication trends, document types, highly cited works, and keyword clusters. The study contributes a conceptual synthesis for strengthening school-based professional learning and SDGs-oriented educational transformation.